Statin treatment and stroke outcome in the stroke prevention by aggressive reduction in cholesterol levels (SPARCL) trial - Goldstein, Larry B.; Amarenco, Pierre; Zivin, Justin; Messig, Michael; Altafullah, Irfan; Callahan, Alfred; Hennerici, Michael G.; MacLeod, Mary J.; Sillesen, Henrik; Zweifler, Richard; Michael, K.; Welch, A. (Stroke, 2009)
Background and Purpose: Laboratory experiments suggest statins reduce stroke severity and improve outcomes. The Stroke Prevention by Aggressive Reduction in Cholesterol Levels (SPARCL) trial was a placebo-controlled, randomized trial designed to determine whether treatment with atorvastatin reduces strokes in subjects with recent stroke or transient ischemic attack (n=4731). We analyzed SPARCL trial data to determine whether treatment favorably shifts the distribution of severities of ischemic cerebrovascular outcomes.Methods— Severity was assessed with the National Institutes of Health Stroke Scale, Barthel Index, and modified Rankin Scale score at enrollment (1 to 6 months after the index event) and 90 days poststroke in subjects having a stroke during the trial.Results— Over 4.9 years, strokes occurred in 576 subjects. There were reductions in fatal, severe (modified Rankin Scale score 5 or 4), moderate (modified Rankin Scale score 3 or 2), and mild (modified Rankin Scale score 1 or 0) outcome ischemic strokes and transient ischemic attacks and an increase in the proportion of event-free subjects randomized to atorvastatin (P<0.001 unadjusted and adjusted). Results were similar for all outcome events (ischemic and hemorrhagic, P<0.001 unadjusted and adjusted) with no effect on outcome hemorrhagic stroke severity (P=0.174 unadjusted, P=0.218 adjusted). If the analysis is restricted to those having an outcome ischemic stroke (ie, excluding those having a transient ischemic attack or no event), there was only a trend toward lesser severity with treatment based on the modified Rankin Scale score (P=0.0647) with no difference based on the National Institutes of Health Stroke Scale or Barthel Index.Conclusion— The present exploratory analysis suggests that the outcome of recurrent ischemic cerebrovascular events might be improved among statin users as compared with nonusers.
Gesehen am 17.03.2021